Osteocytes and Bone Metastasis - Riquelme, Manuel A.; Cardenas, Eduardo R.; Jiang, Jean X. (Frontiers in Endocrinology, 2020)
Bone is the most frequent site of breast cancer and prostate cancer metastasis, and one of the most common sites of metastasis for many solid tumors. Once cancer cells colonize in the bone, it imposes a major clinical challenge for the treatment of the disease, and fatality rates increase drastically. Bone, the largest organ in the body, provides a fertile microenvironment enriched with nutrients, growth factors and hormones, a generous reward for cancer cells. Dependent on cancer type, cancer cells can cause osteoblastic (bone forming) or osteolytic lesions to promote the net resorption and/or release of growth factors from the bone extracellular matrix. These processes activate a “vicious cycle”, leading to disruption of bone integrity and promoting cancer cell growth and migration. Cancer cells influence the bone microenvironment favoring their colonization and growth. In order to metastasize to the bone, cancer cells must first migrate from the site of origin, and once established within the bone, they must overcome the dormant inducing effects of resident cells. If successful, cancer cells can then colonize and continually disrupt bone homeostasis that is primarily maintained by osteocytes, the most abundant bone cell type. For example, it has been shown that exercise induces osteocytes to release anabolic factors that inhibit osteoclast resorptive activity, promote dormancy and the release of anti-cancer factors that inhibit breast cancer cell metastasis. In this review, we will summarize recent research findings and provide mechanistic insights related to the role of osteocytes in osteolytic metastasis.